Nomination and hibah issues in Malaysian takaful (Islamic insurance) industry - Htay, Sheila Nu Nu; Syed, Ahmed Salman (2013)
Takaful has been introduced as a replacement for conventional insurance. However, there are still some unresolved issues in Islamic life insurance (family takaful) when the participants choose a person as either nominee or recipient of gift (hibah). In Malaysia, the Shariah Advisory Council (SAC) have come out with the resolution which states that the participants are allowed to choose the nominee or the recipient of hibah, provided that all the requirements must be clearly stated in the contract. However, some of the shariah scholars do not agree with these resolutions and hence, it is suggested to further look at these issues again to bring the fairness and justice to all involved parties.